P354 GENDER DIFFERENCES IN EPIDEMIOLOGY OF A CORONARY CARE UNIT HUB IN COVID ERA. (18th May 2022) - Frascaro, F; Cardelli, SL; Bugani, G; Sciarra, F; Zagnoni, S; Canovi, L; Dal Passo, B; De Carolis, B; Zanarelli, L; Piscitelli, L; Colletta, M; Casella, G
Abstract: Background: The attention about sex disparities in Cardiology has grown in the last few years. Women are still often under–represented in cardiovascular randomised clinical trials (RCTs) and several studies have shown later diagnosis, less aggressive treatments and poor prognosis among women, even though hospitalized in the coronary care unit (CCU). Objective: To analyze gender–related differences and their relationships with prognosis among patients admitted to a contemporary CCU Hub. Methods: Between 1st March 2021 and 30th November 2021, we prospectively collected the data of patients admitted to the II level CCU of Maggiore Hospital in Bologna. Results: The clinical characteristics of 458 enrolled patients are shown in Table 1. Women represent 32% of the population, are older (p < 0.001) and have been admitted to the CCU mainly for acute coronary syndrome (ACS) (43%) or bradyarrhythmias (23%); men for ACS (57.5%) or heart failure (11.3%). Among patients with ACS, 82% of women underwent coronary angioplasty – both primary and non–primary– versus 88.1% of men (p = 0.276). Females have fewer cardiovascular risk factors and comorbidities than their male counterparts. In CCU, women received similar treatments to men (except for increased use of parenteral nutrition). Similarly, the prevalence of ischemic, haemorrhagic and septic complications was the same between the sexes. The rate of women's mortality in CCU was 1.4%, which increases to 4.8% at 30 days, similar to men's mortality (1.9% versus 3%, respectively). Conclusions: The study demonstrates that one third of the population of a CCU Hub is represented by women, older and more often hospitalized for ACS. These women receive the same treatments as men, including coronary revascularization. There were no differences about gender prognosis, despite a higher trend towards mortality in females after discharge from the CCU. Therefore, studies where women are more represented are needed, in order to obtain precise indications on how to modulate clinical management according to gender.